PI 3-kinases and lipid messengers - Vanhaesebroeck, Bart (Henry Stewart Talks, 2020)
Phosphoinositide lipids and their metabolism, Lipid second messengers produced by PI 3-kinases (PI3Ks), PI3K lipids transduce signals via binding to lipid-binding modules in proteins, Multiple PI3K isoforms with specific biological functions in mammals, Aberrant PI3K activation in cancer, overgrowth and immunity, Clinical trials with PI3K pathway inhibitors, Approval and Challenges for PI3K inhibitors in cancer treatment